La quête du Graal des libéraux-démocrates britanniques : la réforme du mode de scrutin - Cynthia Boyer (Les Cahiers de Framespa)
The lack of proportional representation inherent in the British electoral system has generated much controversy. For several decades now the electoral system reform has spearheaded the claims of the Liberal Party and of their spiritual heirs, the Liberal Democrats (LibDems). Early on, the core identity of the Party had become entertwined with the concept, arousing passions and hereby gaining exposure on the political scene. The present article aims to analyse the specific features of the British electoral system, and subsequently to focus on the genesis of the referendum on electoral system reform which was held on 5th May 2011. Lastly we will consider the results of the referendum surveys as well as the scope of their political impact.